2019
DOI: 10.1530/eje-19-0184
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: Bone disorders associated with acromegaly: mechanisms and treatment

Abstract: Growth hormone (GH) and insulin-like growth factor-I (IGF-I) exert physiological actions on the skeleton throughout life, by stimulating longitudinal bone growth in children, the acquisition of bone mass during adolescence and the maintenance of skeletal architecture in adults. When GH and IGF-I are secreted in excess, bone remodeling is enhanced leading to deterioration of bone microstructure and impairment of bone strength. Indeed, acromegaly causes skeletal fragility, and vertebral fractures are reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 131 publications
(191 reference statements)
1
44
0
3
Order By: Relevance
“…Biochemically active disease is generally associated with a higher risk of vertebral fractures (VF) [19,24]. One study [25] involved 55 patients treated with pasireotide long acting release (LAR) or pegvisomant who had been previously uncontrolled on octreotide LAR or lanreotide for at least 6 months, 42% of whom had VFs at baseline.…”
Section: What's Newmentioning
confidence: 99%
“…Biochemically active disease is generally associated with a higher risk of vertebral fractures (VF) [19,24]. One study [25] involved 55 patients treated with pasireotide long acting release (LAR) or pegvisomant who had been previously uncontrolled on octreotide LAR or lanreotide for at least 6 months, 42% of whom had VFs at baseline.…”
Section: What's Newmentioning
confidence: 99%
“…This seems paradoxical given that IGFs are required for normal bone development [76]. However, excess IGF-1 secretion has been shown to compromise bone integrity and microstructure, leading to increased risk of vertebral fracture [77]. IGFs are also important for the growth and survival of cardiomyocytes, and untreated acromegaly can cause hypertrophic cardiomyopathy leading to cardiac failure [78].…”
Section: Disease States Characterized By Igf Axis Activationmentioning
confidence: 99%
“…Previous research showed a controversial effect of excess GH/IGF-I on trabecular and cortical bone in acromegaly [36]. Kuzma et al [37] published the first study using 3D-SHAPER software in acromegaly and found that regardless of the presence of vertebral fractures, acromegaly patients had less trabecular bone, while cortical density was only decreased in those with vertebral fractures.…”
Section: Cortical and Trabecular Bone Differences Assessed By 3d-dxamentioning
confidence: 99%